An acoustic perspective on 45 years of infant speech perception. II. Vowels and suprasegmentals. Issue 5 (26th February 2020) - Narayan, Chandan R.
Abstract: In this two‐part review we examine the major results from infant consonant (Part 1), vowel, and suprasegmental (Part 2) discrimination research over the past 45 years from an acoustic perspective —an exegesis of the developmental perception literature that appeals to both acoustic aspects of speech contrasts and historically relevant typological facts about sound systems of the world's languages. We argue that infants' speech discrimination abilities are best viewed through a lens that considers both synchronic and diachronic aspects of the particular speech contrast. The key to this approach is the notion that acoustic–perceptual salience, or the relative separation of speech categories along perceptually relevant acoustic dimensions and corresponding discrimination performance in adults, is reflected in both infant's perceptual performance and patterns observed in phonological typology and history. The present review highlights challenges offered by four decades of literature, identifies broad patterns in infant vowel perception according to the acoustic properties of speech contrasts, and offers linguistically motivated explanations and directions for future research into the nature of young infants' discrimination abilities.